a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(x1))) → B(a(b(a(x1))))
B(b(x1)) → A(x1)
A(a(b(x1))) → A(x1)
A(a(b(x1))) → A(b(a(x1)))
A(a(b(x1))) → B(a(x1))
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(x1))) → B(a(b(a(x1))))
B(b(x1)) → A(x1)
A(a(b(x1))) → A(x1)
A(a(b(x1))) → A(b(a(x1)))
A(a(b(x1))) → B(a(x1))
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
A(a(b(x0))) → B(a(b(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(x1))) → A(b(a(x1)))
A(a(b(x1))) → B(a(x1))
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(a(b(x0))))) → A(b(b(a(b(a(x0))))))
A(a(b(x0))) → A(b(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(a(b(x0))))) → A(b(b(a(b(a(x0))))))
A(a(b(x0))) → A(b(x0))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(x1))) → B(a(x1))
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(a(b(x0))))) → A(b(b(a(b(a(x0))))))
A(a(b(x0))) → A(b(x0))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(b(x0)))) → A(c(a(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(a(b(x0))))) → A(b(b(a(b(a(x0))))))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(b(x0)))) → A(c(a(x0)))
A(a(b(x0))) → B(x0)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(a(b(x0))))) → A(b(b(a(b(a(x0))))))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A.1(a.0(b.1(x1))) → A.1(x1)
A.1(a.0(b.1(x1))) → A.0(x1)
B.0(b.0(x1)) → A.0(x1)
A.1(a.0(b.1(a.0(b.1(x0))))) → B.1(a.0(b.0(b.1(a.0(b.1(a.1(x0)))))))
A.1(a.0(b.1(a.0(b.0(x0))))) → A.0(b.0(b.1(a.0(b.1(a.0(x0))))))
A.1(a.0(b.1(x0))) → B.1(x0)
A.1(a.0(b.1(y0))) → B.0(b.1(a.1(y0)))
B.0(b.1(x1)) → A.0(x1)
B.0(b.1(x1)) → A.1(x1)
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.0(x0)))))))
A.1(a.0(b.1(x0))) → B.1(a.0(b.1(x0)))
A.1(a.0(b.1(x0))) → B.0(x0)
A.1(a.0(b.1(a.0(b.1(x0))))) → A.0(b.0(b.1(a.0(b.1(a.1(x0))))))
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(b.1(a.0(b.1(a.0(x0)))))
A.1(a.0(b.0(x0))) → B.0(a.0(b.0(x0)))
A.1(a.0(b.1(x0))) → B.0(a.0(b.1(x0)))
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.1(x0)))))))
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(b.1(a.0(b.1(a.1(x0)))))
A.1(a.0(b.1(a.0(b.0(x0))))) → B.1(a.0(b.0(b.1(a.0(b.1(a.0(x0)))))))
A.1(a.0(b.0(x0))) → B.1(a.0(b.0(x0)))
A.1(a.0(b.0(x0))) → B.0(x0)
A.1(a.0(b.0(y0))) → B.0(b.1(a.0(y0)))
A.1(a.0(b.0(x1))) → A.0(x1)
c.1(x0) → c.0(x0)
a.1(a.0(b.1(x1))) → b.1(a.0(b.1(a.1(x1))))
b.0(b.0(x1)) → c.1(a.0(x1))
b.1(x0) → b.0(x0)
b.0(b.1(x1)) → c.1(a.1(x1))
a.1(x0) → a.0(x0)
a.1(x1) → x1
a.0(x1) → x1
a.1(a.0(b.0(x1))) → b.1(a.0(b.1(a.0(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ SemLabProof2
↳ QTRS Reverse
A.1(a.0(b.1(x1))) → A.1(x1)
A.1(a.0(b.1(x1))) → A.0(x1)
B.0(b.0(x1)) → A.0(x1)
A.1(a.0(b.1(a.0(b.1(x0))))) → B.1(a.0(b.0(b.1(a.0(b.1(a.1(x0)))))))
A.1(a.0(b.1(a.0(b.0(x0))))) → A.0(b.0(b.1(a.0(b.1(a.0(x0))))))
A.1(a.0(b.1(x0))) → B.1(x0)
A.1(a.0(b.1(y0))) → B.0(b.1(a.1(y0)))
B.0(b.1(x1)) → A.0(x1)
B.0(b.1(x1)) → A.1(x1)
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.0(x0)))))))
A.1(a.0(b.1(x0))) → B.1(a.0(b.1(x0)))
A.1(a.0(b.1(x0))) → B.0(x0)
A.1(a.0(b.1(a.0(b.1(x0))))) → A.0(b.0(b.1(a.0(b.1(a.1(x0))))))
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(b.1(a.0(b.1(a.0(x0)))))
A.1(a.0(b.0(x0))) → B.0(a.0(b.0(x0)))
A.1(a.0(b.1(x0))) → B.0(a.0(b.1(x0)))
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.1(x0)))))))
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(b.1(a.0(b.1(a.1(x0)))))
A.1(a.0(b.1(a.0(b.0(x0))))) → B.1(a.0(b.0(b.1(a.0(b.1(a.0(x0)))))))
A.1(a.0(b.0(x0))) → B.1(a.0(b.0(x0)))
A.1(a.0(b.0(x0))) → B.0(x0)
A.1(a.0(b.0(y0))) → B.0(b.1(a.0(y0)))
A.1(a.0(b.0(x1))) → A.0(x1)
c.1(x0) → c.0(x0)
a.1(a.0(b.1(x1))) → b.1(a.0(b.1(a.1(x1))))
b.0(b.0(x1)) → c.1(a.0(x1))
b.1(x0) → b.0(x0)
b.0(b.1(x1)) → c.1(a.1(x1))
a.1(x0) → a.0(x0)
a.1(x1) → x1
a.0(x1) → x1
a.1(a.0(b.0(x1))) → b.1(a.0(b.1(a.0(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof2
↳ QTRS Reverse
A.1(a.0(b.1(x1))) → A.1(x1)
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.1(x0)))))))
A.1(a.0(b.1(a.0(b.1(x0))))) → B.0(b.1(a.0(b.1(a.1(x0)))))
A.1(a.0(b.1(y0))) → B.0(b.1(a.1(y0)))
A.1(a.0(b.0(x0))) → B.0(x0)
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(a.0(b.0(b.1(a.0(b.1(a.0(x0)))))))
B.0(b.1(x1)) → A.1(x1)
A.1(a.0(b.0(y0))) → B.0(b.1(a.0(y0)))
A.1(a.0(b.1(x0))) → B.0(x0)
A.1(a.0(b.1(a.0(b.0(x0))))) → B.0(b.1(a.0(b.1(a.0(x0)))))
A.1(a.0(b.0(x0))) → B.0(a.0(b.0(x0)))
A.1(a.0(b.1(x0))) → B.0(a.0(b.1(x0)))
c.1(x0) → c.0(x0)
a.1(a.0(b.1(x1))) → b.1(a.0(b.1(a.1(x1))))
b.0(b.0(x1)) → c.1(a.0(x1))
b.1(x0) → b.0(x0)
b.0(b.1(x1)) → c.1(a.1(x1))
a.1(x0) → a.0(x0)
a.1(x1) → x1
a.0(x1) → x1
a.1(a.0(b.0(x1))) → b.1(a.0(b.1(a.0(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
A(a(b(a(b(x0))))) → B(a(b(b(a(b(a(x0)))))))
B(b(x1)) → A(x1)
A(a(b(x0))) → B(a(b(x0)))
A(a(b(x1))) → A(x1)
A(a(b(y0))) → B(b(a(y0)))
A(a(b(a(b(x0))))) → B(b(a(b(a(x0)))))
A(a(b(x0))) → B(x0)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(A(x))) → A1(b(B(x)))
B1(a(a(x))) → A1(b(a(b(x))))
B1(a(b(a(A(x))))) → B1(B(x))
B1(a(A(x))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → A1(B(x))
B1(a(b(a(A(x))))) → A1(b(b(a(B(x)))))
B1(b(x)) → A1(c(x))
B1(a(a(x))) → A1(b(x))
B1(a(b(a(A(x))))) → A1(b(B(x)))
B1(a(A(x))) → B1(B(x))
B1(a(b(a(A(x))))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x))))) → A1(b(a(b(b(a(B(x)))))))
B1(a(b(a(A(x))))) → A1(b(a(b(B(x)))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(b(a(A(x))))) → B1(b(a(B(x))))
B1(a(A(x))) → A1(B(x))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(A(x))) → A1(b(B(x)))
B1(a(a(x))) → A1(b(a(b(x))))
B1(a(b(a(A(x))))) → B1(B(x))
B1(a(A(x))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → A1(B(x))
B1(a(b(a(A(x))))) → A1(b(b(a(B(x)))))
B1(b(x)) → A1(c(x))
B1(a(a(x))) → A1(b(x))
B1(a(b(a(A(x))))) → A1(b(B(x)))
B1(a(A(x))) → B1(B(x))
B1(a(b(a(A(x))))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x))))) → A1(b(a(b(b(a(B(x)))))))
B1(a(b(a(A(x))))) → A1(b(a(b(B(x)))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(b(a(A(x))))) → B1(b(a(B(x))))
B1(a(A(x))) → A1(B(x))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(A(x))) → B1(a(B(x)))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(b(a(B(x))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(B(x)))
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(A(x))) → B1(a(B(x)))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(y0))))) → B1(B(y0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(b(a(A(y0))))) → B1(B(y0))
B1(a(A(x))) → B1(a(B(x)))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(a(x))) → B1(x)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(A(x))) → B1(a(B(x)))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(a(x))) → B1(x)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(A(y0))) → B1(B(y0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(A(y0))) → B1(B(y0))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(a(x))) → B1(x)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(x0))))) → B1(A(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x0))))) → B1(A(x0))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x))))) → B1(a(b(b(a(B(x))))))
B1(a(a(x))) → B1(x)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(b(B(x))))
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(b(a(A(x0))))) → B1(a(A(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(b(a(A(x0))))) → B1(a(A(x0)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(b(a(A(y0))))) → B1(b(B(y0)))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(x0))))) → B1(A(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x0))))) → B1(a(A(x0)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(b(a(A(x0))))) → B1(A(x0))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(x0))))) → B1(a(A(x0)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
B1(a(b(a(A(y0))))) → B1(A(y0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(b(a(A(y0))))) → B1(A(y0))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
B1(a(b(a(A(y0))))) → B1(a(a(c(a(B(y0))))))
Used ordering: Polynomial Order [21,25] with Interpretation:
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(a(x))) → B1(x)
POL( B1(x1) ) = x1
POL( A(x1) ) = x1 + 1
POL( c(x1) ) = 0
POL( b(x1) ) = x1
POL( B(x1) ) = x1 + 1
POL( a(x1) ) = x1
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → a(b(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → b(a(B(x)))
b(B(x)) → A(x)
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(b(x)) → a(c(x))
b(a(a(x))) → a(b(a(b(x))))
a(x) → x
b(a(A(x))) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QTRS Reverse
B1(a(a(x))) → B1(a(b(x)))
B1(a(b(a(A(y0))))) → B1(a(b(b(B(y0)))))
B1(a(b(a(A(y0))))) → B1(b(b(a(B(y0)))))
B1(a(a(x))) → B1(x)
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
b(a(b(a(A(x))))) → a(b(a(b(b(a(B(x)))))))
b(B(x)) → A(x)
b(a(A(x))) → b(a(B(x)))
b(a(A(x))) → A(x)
b(a(A(x))) → a(b(B(x)))
b(a(b(a(A(x))))) → a(b(a(b(B(x)))))
b(a(A(x))) → B(x)
a(x1) → x1
a(a(b(x1))) → b(a(b(a(x1))))
b(b(x1)) → c(a(x1))
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
a(x) → x
b(a(a(x))) → a(b(a(b(x))))
b(b(x)) → a(c(x))